Answer:
![\boxed {\boxed {\sf (-2,0)}}](https://img.qammunity.org/2022/formulas/mathematics/college/350z5q382eimstj07fios3qdwxoqg8sq1k.png)
Explanation:
To solve by substitution we must first isolate 1 variable in an equation.
Let's use the first equation.
![x+3y= -2](https://img.qammunity.org/2022/formulas/mathematics/college/drgfris7yp4jh2u4xp5yngt0hupne7ouij.png)
Subtract 3y from both sides to isolate the variable x.
![x+3y-3y= -2 -3y](https://img.qammunity.org/2022/formulas/mathematics/college/1iymahkdqdunavji3g6l3cct6lboic5bpp.png)
![x= -2 -3y](https://img.qammunity.org/2022/formulas/mathematics/college/5dielgs84rcjsodl21ub9shy32bn5qjsux.png)
Now we can substitute the expression (-2-3y) in for x in the second equation.
![3x+4y= -6](https://img.qammunity.org/2022/formulas/mathematics/college/bq6y6h0sdzhfyb6da8w457owemn2shrvk6.png)
![3(-2-3y)+4y= -6](https://img.qammunity.org/2022/formulas/mathematics/college/8z06w75jnkxpfpgrz878tvie07zkk03zlt.png)
Distribute the 3. Multiply each term inside the parentheses by 3.
![(3*-2)+ (3*-3y)+4y=-6\\-6-9y+4y=-6](https://img.qammunity.org/2022/formulas/mathematics/college/do05tmsnnpwhdgxnhhpevbqqrt4ekfuue1.png)
Combine the like terms on the left side.
![-6-5y= -6](https://img.qammunity.org/2022/formulas/mathematics/college/1v64lqmfmg2m18j25v54av2283rcfnyoke.png)
Add 6 to both sides to isolate the variable.
![-6+6-5y=-6+6\\-5y=0](https://img.qammunity.org/2022/formulas/mathematics/college/9y6nmwrwcaapkcfidnegw3vgbglwdntopi.png)
Divide both sides by -5.
![-5y/-5=0/-5 \\y=0](https://img.qammunity.org/2022/formulas/mathematics/college/vsj8le99q8jemf86vxlp54v7fgoh9kkcj8.png)
Now we know that y is equal to 0 and can substitute it into the first equation and find x.
![x+3(0)=-2](https://img.qammunity.org/2022/formulas/mathematics/college/kffyh34t2s7pl2vhot2wyqu9m8wraa6l1o.png)
![x+0=-2 \\x= -2](https://img.qammunity.org/2022/formulas/mathematics/college/nwy5yufi0023vut0v954memdgvuf6ag3s3.png)
x is equal to -2 and y is equal to 0.